P06.13 Inflammatory cytokine biomarkers identify women with asymptomatic genital infections that increase the risk of hiv infection. (13th September 2015) - Masson, L; Deese, J; Arnold, KB; Little, F; Mlisana, K; Lewis, DA; Van Damme, L; Crucitti, T; Abdellati, S; Mkhize, N; Gamieldien, H; Ngcapu, S; et al.
Abstract : Introduction: Untreated sexually transmitted infections (STIs) and bacterial vaginosis (BV) cause genital inflammation and increased risk of HIV infection. WHO-recommended syndromic STI and BV management is limited as large numbers of women with asymptomatic infections go untreated. The purpose of this study was to evaluate genital cytokine profiles as a biomarker to identify women with asymptomatic, treatable infections. Methods: Luminex was used to measure the concentrations of 42 cytokines in cervicovaginal lavages (CVL) from 227 HIV-uninfected women from Durban, South Africa, and nine cytokines in endocervical swabs from 264 women from Bondo, Kenya and Pretoria, South Africa. Women were screened for BV and treatable STIs ( Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, Mycoplasma genitalium ) using microscopy and molecular assays. Nonparametric receiver operating characteristic curves and logistic regression were used to identify cytokine profiles associated with STIs/BV. Results: In women from Durban, concomitant increased IL-1α and IL-1β and decreased IP-10 concentrations in CVLs predicted the presence of a treatable genital condition, correctly classifying 76% of women (sensitivity 72%, specificity 81%, PPV 86% and NPV 64%). In a separate validation cohort of women from Bondo and Pretoria, IL-1α, IL-1β and IP-10 concentrations in endocervical swabs correctly classified 72% of the participants according to STI/BV status. This approach performed substantially better than clinical signs in both cohorts from Durban (sensitivity 19%, specificity 92%, PPV 79% and NPV 40%) and Pretoria and Bondo (sensitivity 29%, specificity 78%, PPV 68%, NPV 39%). Conclusion: Across two cohorts of women residing in different regions in sub-Saharan Africa, genital IL-1α, IL-1β and IP-10 together was the best immunological predictor of the presence of an STI or BV. Supplementing syndromic management with point-of-care assessment of biomarkers of genital inflammation may improve STI/BV management for women, enabling more effective treatment of asymptomatic infections and potentially reducing their risk of HIV infection. Disclosure of interest statement: This work was supported by a Strategic Health Innovation Partnerships (SHIP) grant from the South African Medical Research Council and grants from the Poliomyelitis Research Foundation (PRF) of South Africa and European and Developing Countries Clinical Trials Partnership (EDCTP). The cohorts were supported by grants from the Comprehensive International Program of Research on AIDS (CIPRA) of the Division of AIDS (DAIDS); National Institute of Allergy and infectious Disease (NIAID); National Institutes of Health (NIH) and US Department of Health and Human Services (DHHS) [grant number U19 AI51794]. FEM-PrEP was conducted under two grants funded by the United States Agency for International Development (USAID): the Contraceptive and Reproductive Health Technologies and Research Utilisation Program (GPO-A-00–05–00022–00), and the Preventive Technologies Agreement (GHO-A-00–09–00016–00). Early support was also provided by the Bill and Melinda Gates Foundation. Gilead Sciences, Inc. donated Truvada® and placebo. LM was supported by the PRF; South African Medical Research Council (MRC); the Carnegie Corporation; the National Research Foundation (NRF) of South Africa and the UCT Clinical Infectious Diseases Research Initiative/Wellcome Trust. No pharmaceutical grants were received in the development of this study.